Foramen of Huschke in North Indians: an anatomical study - Chauhan, Renu; Khanna, Jugesh (International Journal of Research in Medical Sciences, 2017)
Background:The deficiency in the antero-inferior wall of the bony part of external auditory canal (EAC) closes by 5 years of age but if it persists beyond that age it is called foramen of Huschke. Depending on the population studied, persistence of this foramen has been seen in 0-67% of adult crania. Review of literature revealed that no data was available in North Indian population; therefore the present study is being undertaken. Methods:Sixty North Indian adult human crania were examined and the presence of foramen of Huschke was noted. The side to which it belonged to, its shape and size were observed. Size of the foramen was measured using vernier caliper. Results:Out of sixty North Indian adult human crania seen, foramen of Huschke was present in 14 crania. It was observed unilaterally in 10 crania and bilaterally in 4. Although different shapes of the foramen like pin point, pin head, circular, irregular and U shape were observed but in majority of cases it was U shaped. Its size varied from pin point- 10 mm transversely and pin point to 9 mm longitudinally. Conclusion: This study revealed that about 23% of North Indian adult human crania have foramen of Huschke. Persistent foramen of Huschke in the adult life may be involved in different abnormalities of the EAC and may lead to otological complications. Therefore, ENT surgeons should be aware of persistent foramen of Huschke and keep it as one of the possible diagnoses while dealing with patients presenting with otological complications. Also the surgeons should be careful while performing endoscopy of Temporomandibular Joint (TMJ) so that accidental damage of TMJ can be prevented.